Investigation of relationship between interfacial electroadhesive force and surface texture. (9th December 2015) - Guo, J; Tailor, M; Bamber, T; Chamberlain, M; Justham, L; Jackson, M
Abstract: A novel investigation into the relationship between the obtainable interfacial electroadhesive forces and different surface textures is presented in this paper. Different surface textures were generated then characterized based on a recognized areal-based non-contact surface texture measurement platform and procedure. An advanced electroadhesive force measurement platform and procedure were then implemented to measure the obtainable electroadhesive forces on those different surface textures. The results show that the obtained interfacial electroadhesive forces increase with decreasing Sq (root mean square height) value of the substrate surface provided that the difference in Sq between the different substrates is over 5 μ m. Also, the higher the applied voltage, the larger the relative increase in electroadhesive forces observed. However, when the difference of Sq value between different substrate surfaces is below 2 μ m, the obtained interfacial electroadhesive forces do not necessarily increase with decreasing Sq . Furthermore, the obtainable electroadhesive forces are not necessarily the same when the Sq value of two substrate surfaces are the same due to the fact that the direction of the surface texture plays an important role in achieving electroadhesive forces.